Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles

Steady state and time resolved fluorescence quenching and chemical modification studies of a lectin from endophytic fungus fusarium solani - Khan, Feroz; Ahmad, Absar; Khan, Mohammad Islam (Journal of Fluorescence, 2010)
The solute quenching studies of a lectin from endophytic fungus Fusarium solani were carried out using different quenchers such as acrylamide, succinimide, potassium iodide and cesium chloride. The lectin showed emission maximum at 348 nm indicating relative exposure of tryptophan. The quenchable fraction of the fluorophore was 100% with acrylamide, whereas it was only 50% with succinimide. The ionic quenchers iodide and cesium showed opposite effects at different pH. In the case of cesium, raising the pH resulted in increased quenching and accessibility of typtophan residue, while the iodide showed just opposite effect. These studies showed that the single tryptophan residue of the lectin (per monomer) is relatively exposed, and might be in the vicinity of positively charged amino acid residues. Various amino acids of the F. solani lectin were modified using different reagents to obtain information about the hemagglutinating site. The chemical modification studies suggested tyrosine residues can be modified using N-acetylimidazole, which results in complete loss of hemagglutination activity of the lectin. Kinetics of chemical modification suggested involvement of only 2 tyrosine residues. Modification of arginine, cysteine, histidine, lysine, aspartate, glutamate and tryptophan did not result in loss of hemagglutinating activity of the lectin.
Keywords: Chemical modification; fluorescence; Fusarium; Lectin; Quenching; Time-resolved

Simple recovery of intracellular gold nanoparticles from peanut seedling roots - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2015)
Fabrication of inorganic nanomaterials via a biological route witnesses the formation either extracellularly, intracellulary or both. Whereas extracellular formation of these nanomaterials is cherished owing to their easy and economical extraction and purification processes; the intracellular formation of nanomaterials, due to the lack of a proper recovery protocol has always been dreaded, as the extraction processes used so far were tedious, costly, time consuming and often resulting in very low recovery. The aim of the present study was to overcome the problems related with the extraction and recovery of intracellularly synthesized inorganic nanoparticles, and to devise a method to increasing the output, the shape, size, composition and dispersal of nanoparticles is not altered. Water proved to be much better system as it provided well dispersed, stable gold nanoparticles and higher recovery. This is the first report, where intracellular nanoparticles have been recovered using a very cost-effective and eco-friendly approach.
Keywords: gold nanoparticles; Peanut; Recovery; Sonication; Water

Size reduction of bulk alumina for mass production of fluorescent nanoalumina by fungus humicola sp. - Moeez, Sana; Siddiqui, Ejaz Ahmad; Khan, Shadab; Ahmad, Absar (Journal of Cluster Science, 2017)
In recent years, nanomaterials have made their way into hundreds of biomedical, life-sciences and technological applications. One such nanomaterial of extreme importance is nanoalumina (Al2O3 nanoparticles). This nanomaterial is an epitome of diversity with applications exhibited in the fields of catalysis, cosmetics, theranostics, energy generation, biosensors, drug-delivery, tumor-regression, etc. However, problems persist in terms of biocompatibility, cost-effectiveness, reproducibility and mass-production of nanoalumina by the presently existent physical, chemical and biological methodologies. Herein, we for the first time are presenting a top-down biofabrication method by which size reduction of commercial bulk alumina/aluminum oxide (5 A mu m) into nanoalumina (5-25 nm) is carried out by a thermophilic fungus Humicola sp. within 96 h of reaction at just 50 A degrees C. The so-formed nanoalumina is highly stable, water dispersible, fluorescent and natural protein capped; characterization engaged standard techniques. These nanoparticles exhibit anti-bacterial properties against Gram-positive Bacillus subtilis strain and may serve as broad spectrum bactericidal agents. We believe that our novel top-down approach may be extensively used in the facile, inexpensive, eco-friendly and reliable fabrication of abundant quantities of nanomaterials of different chemical compositions, sizes and shapes with better control and predictability over the properties as derived from their substrates. The mechanistic aspect of said protocol is underway.